2017
DOI: 10.3748/wjg.v23.i31.5650
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy in patients with hepatocellular carcinoma: Circulating tumor cells and cell-free nucleic acids

Abstract: Hepatocellular carcinoma (HCC), with its high incidence and mortality rate, is one of the most common malignant tumors. Despite recent development of a diagnostic and treatment method, the prognosis of HCC remains poor. Therefore, to provide optimal treatment for each patient with HCC, more precise and effective biomarkers are urgently needed which could facilitate a more detailed individualized decision-making during HCC treatment, including the following; risk assessment, early cancer detection, prediction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 194 publications
0
85
0
Order By: Relevance
“…ctDNA is one of the targets in liquid biopsies and carries information on tumor‐specific genetic or epigenetic alterations. DNA methylation is one of these epigenetic alterations, and several studies have investigated ctDNA methylation in various genes . In this study, we focused on SEPT9 methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ctDNA is one of the targets in liquid biopsies and carries information on tumor‐specific genetic or epigenetic alterations. DNA methylation is one of these epigenetic alterations, and several studies have investigated ctDNA methylation in various genes . In this study, we focused on SEPT9 methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Methylated ctDNA is among the most intensively investigated liquid biopsy targets. Because methylation changes in ctDNA occur early in carcinogenesis, numerous studies have evaluated the diagnostic performance of methylated genes, including cyclin‐dependent kinase inhibitor 2A ( CDKN2A ), Ras association domain family 1 isoform A ( RASSF1A ), and glutathione S‐transferase pi 1 ( GSTP1 ), in patients with HCC . However, the clinical usefulness of these methylated ctDNA tests in HCC remains limited.…”
mentioning
confidence: 99%
“…Several studies have analysed the role of CTCs as a marker to predict survival, recurrence or treatment response in different kinds of tumors [53,57,58] . The presence of CTCs was reported for the first time in 1869 into the blood of a man with metastatic cancer [59] .…”
Section: Ctcsmentioning
confidence: 99%
“…. Numerous studies have shown the potential utility of circulating cancer byproducts detection from which we could extract molecular information about primary tumors [51][52][53][54] . The liquid biopsy could be conducted in repeated samples providing accessible, accurate and dynamic information to evaluate the tumor status.…”
Section: Serpinb3mentioning
confidence: 99%
See 1 more Smart Citation